Visual Public-Key Cryptosystems. - Samsudin, Azman (Universiti Sains Malaysia, 2012)
Many public-key cryptosystems are being used in our daily lives to attain privacy, authenticity, integrity and non-repudiation. However, most of the existing public-key algorithms are based on complex mathematical computations. Until recently, building a highly secured public-key cryptosystem without utilizing complex computations has been a serious challenge, making it necessary for investigations to develop new cryptography methods. Visual cryptography is special because the scheme requires visual inspection or the equivalence of simple Boolean computation and therefore, does not require complex computations.